Meningkatkan kualitas proses pembelajaran dalam pelatihan penelitian tindakan kelas - Ilham Minggi; Usman Mulbar; Nasrullah Nasrullah; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program is carried out by the method of providing training and guidance to participants regarding classroom action research (PTK) to improve the quality of the learning process with the aim of (1) to improve the quality of the learning process, (2) participants can implement well compile classroom action research (PTK) , and (3) participants can disseminate or disseminate classroom action research (PTK) knowledge. The main target audience for the PKM Program activities are school supervisors, school principals and school teachers in Tinggimoncong sub-district, Gowa district, South Sulawesi province. The results obtained in PKM program activities are increased knowledge and concept of classroom action research (PTK) participants of PKM programs, increased classroom action research skills (PTK) PKM program participants, PKM program participants can make examples and arrange classroom action research (PTK) in class learning, and PKM program participants can implement classroom action research (PTK) in learning in schools. Other results obtained were increased motivation of participants in knowing class action research material (PTK) and high enthusiasm of participants in disseminating or disseminating PKM program results, especially classroom action research material (PTK). Outputs of PKM activities are (1) increasing participant's knowledge regarding activity materials, (2) scientific articles published at national seminars, and (3) publications on PKM implementation on online media.